A multicentre evaluation of oropharyngeal secretion management practices in amyotrophic lateral sclerosis. Issue 1 (2nd January 2017) - McGeachan, Alexander J.; Hobson, Esther V.; Al-Chalabi, Ammar; Stephenson, Jodie; Chandran, Siddharthan; Crawley, Francesca; Dick, David; Donaghy, Colette; Ellis, Cathy M.; Gorrie, George; Hanemann, C. Oliver; Harrower, Timothy; et al.
Abstract: Failure to clear oral secretions can be debilitating for patients with amyotrophic lateral sclerosis (ALS), but the treatment of this symptom is poorly defined and there is no consensus on best practice. The objective of this study was to identify the treatments that are commonly prescribed, and to describe how experienced clinicians manage a patient with treatment resistant symptoms. Twenty-three clinicians were approached, of which 19 from 16 centres across the UK provided case report forms for a total of 119 ALS patients identified as having problematic oral secretions. The use of five anticholinergics, salivary gland botulinum toxin injections, conservative management approaches and carbocisteine were reported. Of the 72 patients who were evaluated following the initiation of a first anticholinergic, 61% had symptomatic improvement. Only 19% of patients achieved symptomatic improvement with the use of an alternative anticholinergic when an initial anticholinergic achieved no symptomatic improvement. Problems with thick and thin secretions often coexisted, with 37% of patients receiving treatment for both types of problem. In conclusion, a variety of treatment options are employed by expert clinicians for problematic oral secretions in ALS patients. The variation in management highlights the need for further prospective research in this area.